ナンキョク シュウカイ キキュウ ニヨル ELF/VLF ホウシャ ノ カンソク - 山岸, 久雄; ヤマギシ, ヒサオ; 三宅, 壮聡; ミヤケ, タケトシ; 岡田, 敏美; オカダ, トシミ; 知野, 明裕; チノ, アキヒロ; 門倉, 昭; カドクラ, アキラ; 海老原, 祐輔; エビハラ, ユウスケ; et al. (2006)
P(論文) 2003年1月,第44次南極観測隊により昭和基地からオーロラ現象を総合的に観測するための南極周回気球が放球された.同一観測機構成の2機の気球は南極大陸を半周する編隊飛行を行い,オーロラ現象の時間と空間変動を分離した観測を行うことを試みた.ここでは同気球に搭載されたELF/VLF帯電磁波動観測機の仕様, 実験経過, 初期観測結果について報告する. Circum-Antarctic balloons were launched from Syowa Station by the 44th Japanese Antarctic Research Experiment team in January 2003. Two balloons equipped with identical instruments were flown in formation around the Antarctic continent, in an attempt to separate temporal and spatial variations of the auroral phenomena. In this paper, we report instrument design, operation and some initial results of the ELF/VLF wave experiment by PPB No. 8 and 10 balloons. departmental bulletin paper